Energy efficient processes of electric motor manufacturing - Kühl, Alexander; Kreitlein, Sven; Höft, Annika; Franke, Jörg (2018 IEEE Texas Power and Energy Conference (TPEC), 2018)

Green factories Bavaria: A network of distributed learning factories for energy efficient production - Kreitlein, Sven; Höft, Annika; Schwender, Sabrina; Franke, Jörg (Procedia CIRP, 2015)
The Green Factory Bavaria project contributes to the ability of Bavarian companies to improve their resource consumption. The main impulses include the knowledge transfer of applied research in the industry and the organization of experience exchange among companies. Therefore, Bavarian-wide so-called Green Factories for energy-efficient production are being developed and expanded, see, for instance, the learning and research platforms at the Technische Universitát in Munich, the Friedrich-Alexander-University Erlangen-Núrnberg as well as at Universities of Applied Sciences in Amberg/Weiden, Ansbach, Coburg, Hof, Nuremberg, and Schweinfurt/Wúrzburg. Together, universities and companies are developing technical solutions and methodological approaches for the reduction of resource consumption and are presenting the latest Green Factories findings, where theoretical training can be made comprehensible through demonstration. The companies are supported through individual consulting services, while internet-based checklists and benchmarking analyzes help to determine the need for action. At each location specific Bavarian-wide coordinated technology priorities as well as cross-cutting issues are presented. Joint activities are processed, thereby ensuring the exchange of information among the institutions as well as with the industry. In the model factories for energy-efficient manufacturing innovative industrial partners shall receive the opportunity to demonstrate advanced techniques and technologies for energy-efficient production in the available laboratory and production areas, develop hand-in-hand with scientists from the participating research institutions, build a network among themselves, and circulate the findings effectively to users and students.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Energy-efficient production; Interdisciplinary research-groups; Knowledge exchange

Robot-Based Assembly of Stators – Methods and Tools to Assembly Windings and Coverplates Robotergestützte Montage von Elektromotorstatoren: Methoden und Werkzeuge zur Montage von Wicklungen und Deckschiebern - Kühl, Alexander; Höft, Annika; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2014)

StroMiS - Studie zur technisch-wirtschaftlichen Analyse der Stromerzeugung aus Mikrokraftwerken in Serienfertigung - Scholz, Michael; Kühl, Alexander; Höft, Annika; Landgraf, Maximilian; Schneider, Michael; Böhm, Ralf; Badel, Gregor; Lothes, Gerald; Angerer, Kerstin; Hohmann, Andrea; Simon, Peter; Konwitschny, Fabian; et al. (2019)